Substance Use Disorder And Treatment Courts in the American Criminal Justice System - Oberman, Steven (Medicine, Law & Society, 2025)
The global issue of drug and alcohol addiction leads to the commission of crimes, wasted lives, and unnecessary deaths. Although judicial systems in every country are positioned to encourage treatment of this disease, the focus is too often on imprisonment. One promising alternative is “Treatment Courts,” a relatively recent program in the United States. This program incentivizes citizens accused of crimes by providing rewards for successful completion. Beyond other benefits, this alternative to confinement provides reduced punishment, and in some instances, even dismissal of the offense. This article explores treatment courts and other emerging American alternatives to imprisonment.